2001
DOI: 10.1016/s1095-6433(00)00357-3
|View full text |Cite
|
Sign up to set email alerts
|

ACTH does not mediate divergent stress responsiveness in rainbow trout

Abstract: Two lines of rainbow trout selected for high (HR) and low (LR) responsiveness to a standardised confinement stressor displayed a sustained divergence in plasma cortisol levels during a 3 h period of confinement (max.: HR: 167 ± 13 ng ml -1 ; LR: 103 ± 8 ng ml -1 ; P < 0.001). However, no significant difference in plasma ACTH levels was evident (max: HR: 153 ± 9 pg ml -1 ; LR: 142 ± 7 pg ml -1 ). Dexamethasone (DEX) was administered to HR and LR fish to block endogenous adrenocorticotropin (ACTH) release. Admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 18 publications
(13 reference statements)
3
30
1
Order By: Relevance
“…For example, CRH may be directly involved in the acquisition of a conditioned response (Croiset et al, 2000;Eckart et al, 1999;Wu et al, 1997). However, we have no evidence that there are differences in hypothalamic CRH secretion in the HR and LR lines -plasma ACTH levels are indistinguishable in the two lines during stress (Pottinger and Carrick, 2001b). In the CNS, selection for divergent stress responsiveness in the HR and LR lines of rainbow trout has resulted in regional divergence in brain monoaminergic activity.…”
Section: Discussionmentioning
confidence: 66%
“…For example, CRH may be directly involved in the acquisition of a conditioned response (Croiset et al, 2000;Eckart et al, 1999;Wu et al, 1997). However, we have no evidence that there are differences in hypothalamic CRH secretion in the HR and LR lines -plasma ACTH levels are indistinguishable in the two lines during stress (Pottinger and Carrick, 2001b). In the CNS, selection for divergent stress responsiveness in the HR and LR lines of rainbow trout has resulted in regional divergence in brain monoaminergic activity.…”
Section: Discussionmentioning
confidence: 66%
“…In this experiment both the "vaccine and stress" group and the "stress and vaccine" group become oversensitive to administration of a weightadjusted dose of ACTH compared with the control group, and the oversensitivity increased with duration of the experiment. Few studies on ACTH sensitivity have been done on fish, however Pottinger and Carrick (2001) showed that two lines of rainbow trout selected for high (HR) and low (LR) responsiveness to a standard crowding test had different responsiveness to weight-adjusted dose of ACTH. The LR strain had significant lower production of plasma cortisol compared to HR strain.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation (ACTH) and dexamethasone (DEX) suppression test was conducted in accordance to previous study by Pottinger and Carrick (2001), with some minor modifications. Briefly, at pre-stress, 4 and 6 weeks after start of the experiment 12 fish per group (a total of 36 fish), were netted from their respective tanks, then anaesthetised (as described above), and injected intraperitoneally with 1 mg kg -1 dexamethasone (SigmaAldrich) in ethanol: phosphate-buffered saline (PBS; 1:3; 1μg μL -l ).…”
Section: Stimulation and Suppression Test Of Hpi-axismentioning
confidence: 99%
“…This is not entirely consistent with emerging data on differences between the lines in behaviour (Pottinger and Carrick, 2001a;Øverli et al, 2002) and in brain monoaminergic profiles (Øverli et al, 2001). A recent study suggests that the interrenal is the site at which HPI divergence is mediated in these lines (Pottinger and Carrick, 2001b) and that therefore differences in behaviour and brain neuroendocrinology can be explained in terms of direct effects of cortisol. The present data do not readily fit this hypothesis and the possibility that selection may have altered, for example, the chromaffin catecholaminergic response to stress must also be considered.…”
Section: Discussionmentioning
confidence: 99%